The association of food consumption and macronutrient intake with dietary climate impact in Finland: considerations on the role of energy intake - Paalanen, Laura; Tapanainen, Heli; Sares-Jäske, Laura; Kaartinen, Niina E.; Saarinen, Merja; Valsta, Liisa (Cambridge University Press, 2026)
Objective: To study (1) the differences in dietary climate impact between sociodemographic groups, (2) the differences in food consumption and macronutrient intake as absolute amounts and in relation to energy intake by dietary climate impact level and (3) food groups as contributors of dietary climate impact. Design: Food consumption and energy and macronutrient intakes were calculated based on two non-consecutive 24-hour dietary recalls. Dietary climate impact was calculated using national coefficients produced with life cycle assessment. Regression analysis was used to test the mean differences between sociodemographic groups and sex-specific dietary climate impact tertiles. Setting: Finnish national food consumption survey FinDiet 2017. Subjects: In total, 565 men and 682 women (age 18–74) after exclusion of energy under-reporters. Results: The mean daily dietary climate impact was higher in men than in women (5·6 v. 4·0 kg CO2eq) and in younger age group (18–44 years) than in older age group (65–74 years). The association of food consumption and dietary climate impact was mainly different for food consumption as absolute amounts (g/d) and in relation to energy (g/MJ). In relation to energy, the consumption of animal-based foods was higher and plant-based foods lower in the highest dietary climate impact tertile compared with the lowest tertile. Red and processed meat was a major contributor to dietary climate impact. Conclusion: Our study emphasises the importance of considering food consumption and nutrient intake both as absolute amounts and in relation to energy intake. Our findings support the advantages of plant-based diets in being both healthier and more climate-friendly.
Keywords: sustainability; food consumption; energy intake; dietary climate impact; sociodemographic differences